Sacred sites and the colonial encounter : a history of meaning and memory in Ghana - Greene, Sandra E., 1952- (Indiana University Press, 2002)
"Greene gives the reader a vivid sense of the Anlo encounter with western thought and Christian beliefs ... and the resulting erasures, transferences, adaptations, and alterations in their perceptions of place, space, and the body."--Emmanuel AkyeampongSandra E. Greene reconstructs a vivid and convincing portrait of the human and physical environment of the 19th-century Anlo-Ewe people of Ghana and brings history and memory into contemporary context. Drawing on her extensive fieldwork, early European acc